2021
DOI: 10.1037/ser0000493
|View full text |Cite
|
Sign up to set email alerts
|

Culturally sensitive clinical practices: A mixed methods study.

Abstract: The purpose of this mixed methods study was to discover if and how clinicians integrate cultural factors into treatment, what specific 'culturally sensitive' practices clinicians utilize, and who clinicians use these practices with. In Study 1(N ϭ 9) qualitative interviews were conducted with psychologists who shared information about the culturally sensitive clinical practices that they utilize. Based on the results from Study 1, a survey was created for Study 2 and completed by 142 psychologists. There were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The disclosure of information required to apply for DACA, combined with uncertainty of future immigration reform, leaves applicants and their families at risk for future deportation. The possibility of "outing" undocumented family members creates a sense of fear among DACA recipients (Benuto et al, 2018). The 2017 executive order that prioritized all undocumented persons for deportation highlights the risks associated with applying for DACA (Trump, 2017).…”
Section: The Liminality Of Dacamentioning
confidence: 99%
“…The disclosure of information required to apply for DACA, combined with uncertainty of future immigration reform, leaves applicants and their families at risk for future deportation. The possibility of "outing" undocumented family members creates a sense of fear among DACA recipients (Benuto et al, 2018). The 2017 executive order that prioritized all undocumented persons for deportation highlights the risks associated with applying for DACA (Trump, 2017).…”
Section: The Liminality Of Dacamentioning
confidence: 99%
“…This information is then used to make cultural adaptations as needed (Benuto et al, 2020). Clinicians may wish to review culturally-specific resources when working with clients from diverse backgrounds (i.e., Benuto et al, 2014, 2020).…”
Section: Recommendations To Clinicians and Studentsmentioning
confidence: 99%
“…This may be exacerbated in certain cultural contexts and with specific populations. Benuto, Newlands, Singer, Casas, & Cummings (2019). explored what specific culturally sensitive clinical practices practitioners engage in. Among these practices were logistical accommodations (including accommodations for the client based on his or her abilities), exhibiting flexibility, and making adjustments to treatment if the client is not improving.…”
Section: Recommendations To Clinicians and Studentsmentioning
confidence: 99%
“…While the intention of the clinician working on this case was not to culturally adapt an intervention, the adjustment to treatment to meet the needs of the client could be construed as such. Benuto, Newlands, Singer, Casas, and Cummings (2019) examined culturally sensitive clinical practices among psychologists and found that it is common for psychologists to make adjustments to treatment. Indeed, Koslofsky and Domenech Rodriguez (2016) discussed how, while in the context of the research arena (via grant-funded research), interventions are formally culturally adapted.…”
Section: Recommendations To Clinicians and Studentsmentioning
confidence: 99%
See 1 more Smart Citation